HUBUNGAN ANTARA KECANDUAN INTERNET DENGAN PERILAKU PHUBBING PADA SISWA-SISWI SMA NEGERI 6 SEMARANG - Yossiandry Mikha; Lucy Hariadi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas AKI Semarang, 2023)
This research aims to find out whether there is a relationship between internet addiction and phubbing behavior in students. This research was conducted on students of SMAN 6 Semarang with a total of 387 research subjects, consisting of 174 men and 213 women. Data collection tools are the Internet Addiction Scale which consists of 20 items and the Phubbing Scale which consists of 15 items. Data analysis was carried out using the Spearman Rank correlation statistical technique, with the help of the SPSS version 23 statistical program. From the results of research data analysis, the correlation value between internet addiction and phubbing behavior was obtained ? = 0.714% with significance = 0.000 (p<0.01). This shows that there is a positive and very significant relationship between internet addiction and phubbing behavior. This means that the higher a person's level of internet addiction, the higher the level of phubbing behavior they show in their social interactions. Conversely, the lower a person's level of internet addiction, the lower the level of phubbing behavior they show in their social interactions. Keywords : internet addiction, phubbing behavior